Increase of Traction Forces in Head of a Train above Current Limit in the Network of Správa Železnic (Current Problems in Rail Vehicles, 2025)
Since the 1960s, a traction force limit at the head of the train of 350 kN has been applied on the Czech railway network. Compared to neighbouring countries, this limit is relatively low and negatively impacts freight transport efficiency. Therefore, Správa železnic initiated steps to revise relevant regulations and increase the traction force limit. One aspect addressed in cooperation with VÚKV during 2023–2024 was the interaction between vehicle and track and the running safety under traction forces exceeding 350 kN. The study began with theoretical analyses based on calculations and computer simulations of running dynamics. In the second phase, a test run was conducted with a train set capable of exceeding the current traction limit, with included an instrumented freight wagon equipped to measure key parameters (e.g., wheel forces via an instrumented wheelset and coupler forces at both ends). This paper summarizes the work carried out, key findings from the testing, and the resulting conclusions.
Keywords: traction force; screw coupler; safety against derailment; vehicle-track interaction; instrumented wheelset; freight transport; linear regression